1998
DOI: 10.1021/ja981730y
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Electrografting of Polymers onto Transition Metal Surfaces through Solvent vs Monomer Adsorption

Abstract: Electropolymerization of methacrylic monomers opens the possibility of chemically grafting a wide range of polymers onto transition metal surfaces. In this work, the electropolymerization of polyacrylonitrile and polyethyl acrylate is studied in different solvents; we experimentally confirm that the choice of solvent is a critical parameter for obtaining electrografted polymers. A density-functional theory−based study modeling the interaction of solvent (acetonitrile, dimethylformamide, and pyridine) or monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 82 publications
3
34
0
Order By: Relevance
“…(a) If we assume that the first term in the square brackets in eq 7 is larger than the second, then we get (9) (b) If we assume that the repulsion between the blocks (second term in eq 7) is the dominant factor in the spreading of the drops, then we obtain (10) On the basis of these expressions, we define a new parameter ∈, the polymeric control parameter, to be N B /N A 11/6 in the first limit (eq 9), or N B /N A 5/6 in the second limit (eq 10). In both these equations, Ψ is a correction term that depends only on the monomeric interfacial energies and on the particular geometry of the adsorption morphologies.…”
Section: (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…(a) If we assume that the first term in the square brackets in eq 7 is larger than the second, then we get (9) (b) If we assume that the repulsion between the blocks (second term in eq 7) is the dominant factor in the spreading of the drops, then we obtain (10) On the basis of these expressions, we define a new parameter ∈, the polymeric control parameter, to be N B /N A 11/6 in the first limit (eq 9), or N B /N A 5/6 in the second limit (eq 10). In both these equations, Ψ is a correction term that depends only on the monomeric interfacial energies and on the particular geometry of the adsorption morphologies.…”
Section: (5)mentioning
confidence: 99%
“…[6][7][8][9][10][11] Moreover, the polymer adsorption is facilitated by an interaction-multiplier effect, which is unique to chain molecules. [12][13][14] Any interaction that occurs with one segment is multiplied by the large number of identical segments in the macromolecule to generate a large intermolecular effect.…”
Section: Introductionmentioning
confidence: 99%
“…That the grain size increases with monomer concentration is not the consequence of an increase in the chain grafting density. Indeed, Crispin et al have shown [14] that AN is much more strongly adsorbed onto Ni than the solvent molecules. This suggests that when the nickel electrode is put in the electrochemical medium the 6 metal surface gets covered by a monolayer of AN molecules, whatever the solvent and the AN concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Solvation of the PEA chains by the electrolytic solution (AN/DMF) is only part of the explanation. According to theoretical calculations by Crispin et al [14], EA is less strongly adsorbed onto nickel than AN and thus less prone than AN to displace the solvent molecules for being adsorbed onto the cathode sites. Thus, the Ni surface, which is thought to be covered by a monolayer of AN molecules in DMF, would not be completely covered by EA at the same concentration (0.5 M) in DMF.…”
Section: Pea Grafting Firstmentioning
confidence: 99%
See 1 more Smart Citation